Properties of Narrow-Gap Cadmium-Based Compounds - Capper, Peter (Institution of Engineering & Technology Books International, Inc. [distributor], 1994)
Annotation This highly structured volume contains sections on growth and device aspects of mercury cadmium telluride (MCT).
Keywords: elektronické knihy; electronic books